OTONOMI DAERAH DAN DESENTRALISASI PENDIDIKAN: (Studi Pada Jenjang Pendidikan Menengah Dinas Pendidikan Kota Sawahlunto) - Novendra Hidayat (Society, 2016)
This study aimed to describe and analyze the implementation of decentralization in educational management in Sawahlunto, specifically in School Based Management (SBM) at the level of secondary education. It uses the concept of decentralization, Educational Management, and School-Based Management (SBM). This study applies a qualitative approach design of descriptive analysis case study and collecting the data by interviewing and documentation. Informants were selected by purposive sampling. The study shows the implementation of decentralization in educational management particularly in the implementation at the level of secondary education must be completed so it can be more optimal. In its implementation efforts, carried out the stages to improve the performance of school management organizations, the management of human resources, teaching-learning process, administrative resources, Educational Services School-Based Management, and Quality Improvement of Education and Manpower Education. The local government is currently implementing the three pillars of educational development. In accordance with the Local Government Work Plan (RKPD), School-Based Management Improvement Program is one of the Educational Department programs. It is one form of decentralization in educational management, the implementation is expected to improve the quality of education in Sawahlunto at every level of education